2014
DOI: 10.1021/la404567b
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hg-Triggered Gelation via Structural Modifications

Abstract: The relationship between chemical structure and gelation ability was examined for a series of nine Hg-containing compounds. Both solid-state properties (dissolution enthalpies/entropies and packing structure) and gel properties (strength, morphology, cation selectivity, and anion tolerance) were examined. Overall, the results reveal a complex relationship between chemical structure and properties. The remediation potential of these Hg-triggered gelations was also investigated, revealing that >98% of the Hg(2+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The library approach simply involves generating a large number of similar molecules and then determining which form gels. [28][29][30] This brute force approach is often successful in finding gelators, but it is Figure 1. Uses of Low-Molecular-Weight Gels Cartoon showing some the potential uses of low-molecular-weight gelators, including cell culture and differentiation with non-harmful release from the gelled material, photoresponsive semiconducting gel fibers, high loading of a drug particle with a targeted release, slow and controlled drug release upon addition of a stimulus, water purification by the removal of heavy metals, and the control of polymorph by changing the gel network.…”
Section: Introductionmentioning
confidence: 99%
“…The library approach simply involves generating a large number of similar molecules and then determining which form gels. [28][29][30] This brute force approach is often successful in finding gelators, but it is Figure 1. Uses of Low-Molecular-Weight Gels Cartoon showing some the potential uses of low-molecular-weight gelators, including cell culture and differentiation with non-harmful release from the gelled material, photoresponsive semiconducting gel fibers, high loading of a drug particle with a targeted release, slow and controlled drug release upon addition of a stimulus, water purification by the removal of heavy metals, and the control of polymorph by changing the gel network.…”
Section: Introductionmentioning
confidence: 99%
“…During these studies, we discovered that several dipeptides underwent solid–solid transformations during the solubility measurements. Graduate student Kelsey (King) Carter later observed similar solid–solid transformations with our Hg complexes, precluding further analysis [ 35 ]. Ultimately, our take-home message was that strong intermolecular interactions and weak solvent interactions are important in gelation.…”
Section: Reviewmentioning
confidence: 99%
“…While most of our sensors were designed with this criterion in mind, we were sometimes surprised to find slower and/or lower yielding reactions than reported. In these cases, we evaluated the stability of the reaction intermediates [ 38 ], measured reaction rates for both the desired and undesired products [ 39 ] and optimized the conditions to accelerate the desired transformations [ 34 – 35 ]. We learned from our early efforts that generating highly sensitive sensors required analytes that were efficient catalysts.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is imperative to screen suitable Hg 2+ detection systems with high selectivity, sensitivity and reliability. Many methods have been developed specifically for Hg 2+ ion detection (Coronado et al, 2005;Kim et al, 2010Kim et al, , 2012Misra & Shahid, 2010;Cheng et al, 2011;Dalapati et al, 2011;Tian & Ihmels, 2011;Ren et al, 2012;Chen et al, 2013;Goswami et al, 2013;Lu et al, 2013;Madhu et al, 2013;Shafeekh et al, 2013;Bera et al, 2014;Carter et al, 2014;Huang et al, 2014;Li et al, 2014;Thirupathi et al, 2014). For example, Thirupathi et al (2014) reported a ratiometric fluorescence chemosensor based on tyrosine derivatives for monitoring mercury ions in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%